Faktor-Faktor Yang Berhubungan Dengan Keluhan Nyeri Punggung Bawah Pada Petani Lansia Di Desa Tempang Dan Desa Tempang Tiga - Lumenta, Tesalonika Agresi; Bidjuni, Hendro; Kristamuliana (Mapalus Nursing Science Journal, 2023)
Background: Low back pain is a condition when pain or unpleasant feelings arise and is a major cause of disability that affects work as well as well-being. Aim: The aim of this study was to determine the factors associated with complaints of low back pain in elderly farmers. Method: The method of research used is Retrospective Descriptive. Result: The results of the study using the gamma test, for the variable gender with complaints of low back pain p = 0.024 (p < 0.05). Variable age of starting work with complaints of low back pain p = 0.872 (p> 0.05). Variable body shape with low back pain complaints p = 0.046 (p < 0.05). Variable working period with complaints of low back pain p = 0.122 (p> 0.05). Smoking behavior variable with complaints of low back pain p = 0.021 (p < 0.05). Discussion: Women have a higher prevalence of back pain than men because women do more bending intensity at work. Elderly farmers who have started working in their early teens will get used to low back pain. Elderly people who have a fat body shape are influenced by lifestyles such as food, rest and even work stress. The longer a person's working period, the more accustomed they will feel low back pain. Elderly farmers who smoke will get tired easily in doing work so they can feel pain in the lower back. Conclusion: The conclusion of this study is that there is a relationship between gender, body shape, smoking behavior with complaints of low back pain and there is no relationship between age of starting work, working period with complaints of low back pain.